Tumor Associated Stromal Cells Play a Critical Role on the Outcome of the Oncolytic Efficacy of Conditionally Replicative Adenoviruses - Lopez, Maria Veronica (2009)
The clinical efficacy of conditionally replicative oncolytic adenoviruses (CRAd) is still limited by the inefficient infection of the tumor mass. Since tumor growth is essentially the result of a continuous cross-talk between malignant and tumor-associated stromal cells, targeting both cell compartments may profoundly influence viral efficacy. Therefore, we developed SPARC promoter-based CRAds since the SPARC gene is expressed both in malignant cells and in tumor-associated stromal cells. These CRAds, expressing or not the Herpes Simplex thymidine kinase gene (Ad-F512 and Ad(I)-F512-TK, respectively) exerted a lytic effect on a panel of human melanoma cells expressing SPARC; but they were completely attenuated in normal cells of different origins, including fresh melanocytes, regardless of whether cells expressed or not SPARC. Interestingly, both CRAds displayed cytotoxic activity on SPARC positive-transformed human microendothelial HMEC-1 cells and WI-38 fetal fibroblasts. Both CRAds were therapeutically effective on SPARC positive-human melanoma tumors growing in nude mice but exhibited restricted efficacy in the presence of co-administered HMEC-1 or WI-38 cells. Conversely, co-administration of HMEC-1 cells enhanced the oncolytic efficacy of Ad(I)-F512-TK on SPARC-negative MIA PaCa-2 pancreatic cancer cells in vivo. Moreover, conditioned media produced by stromal cells pre-infected with the CRAds enhanced the in vitro viral oncolytic activity on pancreatic cancer cells, but not on melanoma cells. The whole data indicate that stromal cells might play an important role on the outcome of the oncolytic efficacy of conditionally replicative adenoviruses.